Clinical Efficacy of Repetitive Transcranial Magnetic Stimulation in Recovery of Hand Function Among Stroke Patients: A Scoping Review - Gurav Pooja Ramesh; Manju Devi; Suresh Mani (Talenta Publisher, 2026)
Background: Delayed hand function recovery is common after stroke. Repetitive transcranial magnetic stimulation (rTMS) is an emerging non-invasive brain stimulation technique with potential for post-stroke recovery, particularly for hand function, an area with limited research. Objective: Therefore, the aim of this scoping review was to ascertain the clinical efficacy of rTMS in the recovery of hand function among stroke patients. Methods: A systematic search of PubMed, Cochrane, and ScienceDirect from 2005 to 2023 identified original research on rTMS, stroke, and hand function. The reviewers independently screened articles for eligibility, and data were extracted on rTMS intervention protocols and outcomes. Methodological quality was assessed using PEDro analysis. Results: Of 5423 titles screened, 13 studies met the inclusion criteria and were of excellent quality according to PEDro analysis. The studies used varied rTMS intervention parameters, such as frequencies (1 Hz to 20 Hz), stimulus duration (2 sec to 55 sec), numbers of stimuli (10-1000), and variable rest intervals. Conclusion: Overall, rTMS has a positive and clinically significant effect on hand function recovery, but its intervention parameters vary widely. Therefore, further research is needed to establish standardized treatment guidelines to determine the long-term effects of rTMS on motor hand function recovery.